2018
DOI: 10.1177/1073274818799306
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer, Human Papillomavirus Infection, and Vaccine-Related Knowledge

Abstract: Cervical cancer (CC) has a high incidence and mortality and is accompanied by lack of organized CC screening programs, lack of health-care facilities, and a lack of human papillomavirus (HPV) vaccination among female population in the world, particularly China. We recruited 487 females who visited the outpatient department of the First People’s Hospital of Yunnan Province from November 2015 to January 2016 to complete a standardized-designed questionnaire. We found that only 39.6% of the females knew about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…However, in China, the cognition, development, and application of HPV vaccines still face several challenges. Little knowledge about HPV and their role in cancer development is significantly alarming (23). Contemporary HPV vaccines aim at HPV6, HPV11, HPV16, and HPV18 genotypes, which may not effectively mitigate cervical cancer in regions such as southwest China where HPV52 and HPV58 were more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…However, in China, the cognition, development, and application of HPV vaccines still face several challenges. Little knowledge about HPV and their role in cancer development is significantly alarming (23). Contemporary HPV vaccines aim at HPV6, HPV11, HPV16, and HPV18 genotypes, which may not effectively mitigate cervical cancer in regions such as southwest China where HPV52 and HPV58 were more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Because only 10.9% (39/357) of males and 15.0% (102/676) of females had previous knowledge about HPV and cervical cancer, these results are consistent with a similar study by Naing et al 15 in which they reported that among their study group, few participants had good HPV-related knowledge (14%) and vaccine-related knowledge (8%). Baloch et al 16 determined that 37.9% of women knew about cervical cancer and 16% knew about the HPV vaccine, and Yuanyue et al 17 showed that 13-25% of women knew about cervical cancer and the HPV vaccine, in 2 Chinese studies. Thus, the level of knowledge about HPV and the HPV vaccine was low, and this was comparable to our findings, but there was a difference in the targeted study population.…”
Section: Discussionmentioning
confidence: 99%
“…30 To date, despite the fact that the HPV vaccine has been licensed for over a decade in the United States, a study showed that only near 30% women had heard of HPV only slightly, over half knew about the link of HPV infection with cervical cancer. 31 A recent study that was conducted in the Yunnan province in 2016 reported that approximately 40% of women knew about the role of HPV in cervical cancer development 32 versus 26.5% in a 2015 study that was conducted in the same province. 33 Since the HPV vaccine is now available in the country, more research will need to be conducted to assess the knowledge and understanding of the general public about the HPV vaccine, especially among marginalized groups.…”
Section: General Lack Of Knowledge Of Hpv and Its Link To Cervical Camentioning
confidence: 99%